Tree Species Diversity and Productivity Relationship in the Central Region of Bangladesh - Das, Niamjit; Sarker, Swapan Kumar (Journal of Forests, 2015)
The diversity-productivity relationship has received considerable attention during the past two decades, largely because of the continuous loss of biodiversity. The positive relationship between species diversity and productivity is significant as a credible argument for the conservation of biodiversity. This research was conducted in the central region of Bangladesh to exemplify the relationship between tree species diversity and stand productivity at four mixed plantations. In total 112 sample plots (size - 0.09 ha/plot) of four different mixed species plantations were systematically selected for data collection. After that, regression analysis explained a significantly positive relationship between tree species diversity and productivity at four mixed plantations. This research suggests that having more tree species generally raises plantation productivity. Therefore, this result indicates that mixed species plantations could be the better choice in the degraded and fallow forest lands of Bangladesh.